2019
DOI: 10.1177/1077695819852256
|View full text |Cite
|
Sign up to set email alerts
|

Through Reflective Lenses: Enhancing Students’ Perceptions of Their Media Writing Skills

Abstract: Many national reports have documented students’ writing deficiencies and the need to develop rigorous writing curricula that moves the needle forward in training young professionals to write. The quasi-experimental study described herein explains the effect reflection had on journalistic writing students’ media writing self-perception scores. We found that students who participated in metacognitive reflection exercises after each major journalistic writing assignment scored significantly higher on the writing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Students' average MWSP scores may indicate that they have low MWSPs, which is a critical reality but not different from previous studies (Leggette, Redwine, and Busick 2019;Meier, McCarthy, and Schmeck 1984). Therefore, college faculty, especially those who teach discipline-specific communications and writing courses, should consider integrating curriculum into their courses that focuses on increasing students' perceived and actual writing abilities.…”
Section: Discussion and Recommendationsmentioning
confidence: 90%
“…Students' average MWSP scores may indicate that they have low MWSPs, which is a critical reality but not different from previous studies (Leggette, Redwine, and Busick 2019;Meier, McCarthy, and Schmeck 1984). Therefore, college faculty, especially those who teach discipline-specific communications and writing courses, should consider integrating curriculum into their courses that focuses on increasing students' perceived and actual writing abilities.…”
Section: Discussion and Recommendationsmentioning
confidence: 90%
“…In addition to course content and assignments, faculty could use exercises that allow HIRING STUDENTS: COMMUNICATION INDUSTRY VIEW students to reflect on the communication and decisionmaking skills they used to complete the assignment and on how they could improve their application of such skills. Leggette et al (2020), in their quasi-experiment study, found that students who participated in metacognitive reflection exercises after each major writing assignment had higher writing self-efficacy scores and overall higher media writing self-perception scores. Thus, reflection was one way the students in the Leggette et al (2020) study transformed into career-ready professionals.…”
Section: Discussionmentioning
confidence: 98%
“…Leggette et al (2020), in their quasi-experiment study, found that students who participated in metacognitive reflection exercises after each major writing assignment had higher writing self-efficacy scores and overall higher media writing self-perception scores. Thus, reflection was one way the students in the Leggette et al (2020) study transformed into career-ready professionals.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As scholarship on English education in Korea demonstrates, many students graduating from domestic secondary schools likely encounter substantial shifts upon entering U.S.-style introductory writing courses. My anecdotal familiarity with the communication major's newswriting course (at least at the U.S.-based campus) and my knowledge of scholarship on mass communication pedagogy (see, e.g., Leggette et al, 2020;Massé & Popovich, 1998;Panici & McKee, 1996) prompted me to believe that students would have to shift twice-from narrative and even explicitly creative writing to the argumentative and expository writing featured in the university's general first-year writing courses, and then once again to the specific generic and style exigencies of AP-formatted news reporting. When I expressed that concern to U.S.-native Professor W (interview, May 2016), he concurred briefly but then related that he had contacted several students he knew would be enrolling in his introductory newswriting course the following semester.…”
Section: Double Shift: Writing In Communication At the Asia Campusmentioning
confidence: 99%